Evaluation of wound healing activity of Commiphoramyrrha extract compared with silver sulfadiazine on experimental skin burn healing in rat - orly yadegar; ahmad asghari; saeid hesaraki (Āsīb/shināsī-i Darmāngāhī-i Dāmpizishkī, 2013)
Myrrh, a traditional herbal medicine,is derived from Commiphoramyrrha (Nees) Engl. (Burseraceae) and various other species of Commiphora. It has widely been used in different diseases in India, China, Italy and Greece. Pharmacological studies also have showed that myrrh possesses multiple activities, including anti-inflammatory, cytotoxic, anesthetic, and antimicrobial effects.  There has been no report on the effectiveness of commiphoramyrrha in treating burn wound. Therefore, in this study, we compared the healing times of full thickness burn wounds in rats that received commiphoramyrrha treatment or the standard SSD treatment. This study was carried out on sixty male Wistar albino rats. Grade 3 burn wounds were created on the back of all rats. The animals were randomly divided into four groups, the first group of rats received no medication, the second group received eucerin (negative control), the third group received topical SSD group and the fourth group received 2.5% Commiphoramyrrha in eucerin base.Histological samplings were done on 7th, 14th and 21st days in each group, then all samples transported to the laboratory and H&E and trichrom staining was done. Histopatological evaluation on the 7th, 14th and 21st days showed burn healing to be better in the group which had received CommiphoraMyrrha with respect to other groups, in addition wound healing was significantly better in this group (p